2019
DOI: 10.1002/cam4.2269
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pricing strategy on the costs of oral anti‐cancer drugs

Abstract: Background The soaring costs of anti‐cancer drugs pose a threat to the sustainability of cancer care. The pricing strategy chosen by manufacturers can impact the costs of oral anti‐cancer drugs during dose modifications, but this issue remains under‐recognized in the literature. In general, with the flat pricing strategy, there is a single fixed price for each tablet regardless of dosage strength, whereas with linear pricing, the price of each tablet increases with its dose. We hypothesize that fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The pricing models for oral treprostinil and selexipag are not directly comparable, as oral treprostinil is based on a price-per-dose model, with increased pricing for higher-dosage tablets, whereas selexipag is based on a fixed price that does not vary by dose. While fixed pricing, regardless of dosage, is often perceived as less costly and predictable [29], dose-based pricing can result in lower costs with dose reductions [30]. This study showed that, for oral prostacyclin drugs used in patients with PAH, treprostinil dose-based pricing led to lower pharmacy costs than the fixed pricing associated with selexipag.…”
Section: Discussionmentioning
confidence: 78%
“…The pricing models for oral treprostinil and selexipag are not directly comparable, as oral treprostinil is based on a price-per-dose model, with increased pricing for higher-dosage tablets, whereas selexipag is based on a fixed price that does not vary by dose. While fixed pricing, regardless of dosage, is often perceived as less costly and predictable [29], dose-based pricing can result in lower costs with dose reductions [30]. This study showed that, for oral prostacyclin drugs used in patients with PAH, treprostinil dose-based pricing led to lower pharmacy costs than the fixed pricing associated with selexipag.…”
Section: Discussionmentioning
confidence: 78%
“…O atual modelo de definição de preços brasileiro é focado na proporcionalidade de concentração de princípio ativo, enquanto alguns modelos internacionais são focados no tratamento e, por isso, podem ter preço flat (mesmo preço para apresentações com concentrações diferentes) (Brasil, 2004;Clarivate Analytics, 2020aTruong et al, 2019).…”
Section: Discussionunclassified
“…• Intervention of drug cost management will be effective. others were conducted on the pricing of prescription drugs to reduce costs, [13][14][15][16] and some of them have examined the cost of drugs in the ICU and emergency department. [17][18][19] Reducing the costs of the health system, especially hospitals, has always been a concern for policy makers and managers.…”
Section: Highlightsmentioning
confidence: 99%
“…Accordingly, many studies have been conducted on reducing drug costs. A number of these studies have analysed the cost of antibiotics, 8–12 some others were conducted on the pricing of prescription drugs to reduce costs, 13–16 and some of them have examined the cost of drugs in the ICU and emergency department 17–19 …”
Section: Introductionmentioning
confidence: 99%